Folhas de ora-pro-nobis (Pereskia aculeata Miller): uma fonte nativa de proteína vegetal pouco explorada - Tavares, Laura Médici (Universidade Federal de São Carlos, 2025)
Currently, population growth and global food production have been associated with global climate change and the scarcity of fresh water, for example. In this scenario, there is a global concern regarding the sustainable supply of protein for the coming decades. Brazil is a country with rich flora, including various edible plants with high protein content, such as Pereskia aculeata Miller, also known as ora-pro-nobis (OPN). Thus, this study aimed to extract proteins from OPN leaves and analyze them for their technological characteristics. The process began with the production of flour from OPN leaves through forced circulation. Subsequently, the centesimal composition of this material was performed using official methods, obtaining the following results: the moisture content of OPN leaves (88.2% w/w), and in the flour, lipids (5.6% w/w), proteins (9.4% w/w), ash (17.1% w/w), and total carbohydrates (20.3% w/w), all expressed on a dry basis. To optimize the protein extraction from the leaves, acid-induced precipitation experiments were conducted, varying the pH of the solution (2.0, 3.0, 3.5, and 4.0) to approach the isoelectric point of the leaf proteins, aiming to improve the extraction efficiency. After conducting the tests, the pH chosen for this process was 3.5. Finally, after obtaining the protein concentrate, protein suspensions with concentrations of 1.0% w/w (T1), 2% w/w (T2), and 4% w/w (T3) were prepared, and steady rheological tests were carried out to measure viscosity, as well as oscillatory frequency and temperature scans in the linear viscoelasticity region for all treatments. The results indicated that the fluid exhibited a Newtonian behavior, regardless of the protein concentration in suspension. A maximum viscosity of 1.378 mPa·s-1 was observed for T3. The viscous (G'') and elastic (G') moduli showed slight dependence on frequency for all treatments, with G'' > G'. In none of the protein concentrations tested was the formation of thermal or acid gels observed. Therefore, it is concluded that this study contributes to a deeper understanding of the physicochemical characteristics of the leaf and the behavior of ora-pro-nobis proteins in suspension, evaluating its potential for future applications in the food industry, highlighting a native plant protein source that can be cultivated throughout Brazil.
Ora-pro-nobis leaves (Pereskia aculeata Miller): an underexplored native source of plant-based protein
Keywords: Extração; Viscosidade; Reologia; Varredura de frequência; Varredura de temperatura; Plantas Alimentícias Não Convencionais; Extraction; Viscosity; Rheology; Frequency sweep; Temperature sweep; Non-Conventional Food Plants; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS